Neoadjuvant neratinib promotes ferroptosis and inhibits brain metastasis in a novel syngeneic model of spontaneous HER2(+ve) breast cancer metastasis - Nagpal, Aadya (Breast Cancer Res, 2019)
BACKGROUND: Human epidermal growth factor receptor-2 (HER2)-targeted therapies prolong survival in HER2-positive breast cancer patients. Benefit stems primarily from improved control of systemic disease, but up to 50% of patients progress to incurable brain metastases due to acquired resistance and/or limited permeability of inhibitors across the blood-brain barrier. Neratinib, a potent irreversible pan-tyrosine kinase inhibitor, prolongs disease-free survival in the extended adjuvant setting, and several trials evaluating its efficacy alone or combination with other inhibitors in early and advanced HER2-positive breast cancer patients are ongoing. However, its efficacy as a first-line therapy against HER2-positive breast cancer brain metastasis has not been fully explored, in part due to the lack of relevant pre-clinical models that faithfully recapitulate this disease. Here, we describe the development and characterisation of a novel syngeneic model of spontaneous HER2-positive breast cancer brain metastasis (TBCP-1) and its use to evaluate the efficacy and mechanism of action of neratinib. METHODS: TBCP-1 cells were derived from a spontaneous BALB/C mouse mammary tumour and characterised for hormone receptors and HER2 expression by flow cytometry, immunoblotting and immunohistochemistry. Neratinib was evaluated in vitro and in vivo in the metastatic and neoadjuvant setting. Its mechanism of action was examined by transcriptomic profiling, function inhibition assays and immunoblotting. RESULTS: TBCP-1 cells naturally express high levels of HER2 but lack expression of hormone receptors. TBCP-1 tumours maintain a HER2-positive phenotype in vivo and give rise to a high incidence of spontaneous and experimental metastases in the brain and other organs. Cell proliferation/viability in vitro is inhibited by neratinib and by other HER2 inhibitors, but not by anti-oestrogens, indicating phenotypic and functional similarities to human HER2-positive breast cancer. Mechanistically, neratinib promotes a non-apoptotic form of cell death termed ferroptosis. Importantly, metastasis assays demonstrate that neratinib potently inhibits tumour growth and metastasis, including to the brain, and prolongs survival, particularly when used as a neoadjuvant therapy. CONCLUSIONS: The TBCP-1 model recapitulates the spontaneous spread of HER2-positive breast cancer to the brain seen in patients and provides a unique tool to identify novel therapeutics and biomarkers. Neratinib-induced ferroptosis provides new opportunities for therapeutic intervention. Further evaluation of neratinib neoadjuvant therapy is warranted. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13058-019-1177-1) contains supplementary material, which is available to authorized users.